org.ânica: centro de agricultura familiar de Maranguape - Ponte, Fernanda Marques de Sousa (2018)
The org.ânica, a project elaborated in final graduation project, is developed in the center of Maranguape, state of Ceará, Brazil. The project is based in studies on family agriculture on the state of Ceará and the cities near the state capital, Fortaleza, linking a theoretical basis for a local economy of the city and a creation of a architectonic mark for the valorization of the city center, patrimonial restoration and creation of a new open square. The equipment has an open market, a municipal market, a popular restaurant and a school of gastronomy, working in partnership with the municipal schools of Maranguape, seeking to expand market opportunities and make it possible to professionalize local students.